Perspectives on justice and trust in organizations - Schriesheim, Chester; Neider, Linda L., 1953- (Research in management ;, 2012)
We are living in an age of pervasive distrust, one so severe that journalists discuss the "trust deficit" almost as regularly as they do trade or economic shortfalls. Perceptions of injustice and lack of fairness have increased so much during the years after the economic crash of 2008 that few organizations, both public and private, have been left unaffected. In fact, numerous opinion polls illustrate deep distrust on the part of participants towards political leaders, government organizations, and certainly, business leaders across many industries. Democrats, Republicans, conservatives, liberals, the wealthy, the poor, executives, police officers, managers - the list goes on and on. Some months back, an NBC/WSJ survey showed an eye-popping 82% disapproval rating for the U.S. Congress, the lowest in the history of the poll! With this climate as a backdrop, Volume 9 of the Research in Management series brings together seven chapters written by leading scholars in the field of justice and trust who present new research, models and conceptualizations to provide insights for key issues in this field both from a scholarly perspective as well as pragmatic suggestions for practice.